1998
DOI: 10.1523/jneurosci.18-05-01879.1998
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Regularizes the Phasic Firing Pattern of Rat Hypothalamic Magnocellular Vasopressin Neurons

Abstract: Vasopressin (AVP) magnocellular neurons of hypothalamic nuclei express specific phasic firing (successive periods of activity and silence), which conditions the mode of neurohypophyseal vasopression release. In situations favoring plasmatic secretion of AVP, the hormone is also released at the somatodendritic level, at which it is believed to modulate the activity of AVP neurons. We investigated the nature of this autocontrol by testing the effects of juxtamembrane applications of AVP on the extracellular acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 42 publications
7
106
0
7
Order By: Relevance
“…AVP neurons display in vitro an electrical activity almost comparable with that observed in vivo, characterized by a succession of shorter periods of activity and silence than in vivo (23). Electrical stimulations of isolated neurohypophysial terminals led to the demonstration that the silent and active periods in the firing activity of AVP neurons are equally necessary for optimal release (24,25). SDF-1, as shown here, has various effects on the electrical activity of SON neurons, resulting probably from the heterogeneity of the population recorded or from a variety of actions on the AVP neuronal population (26).…”
Section: Discussionmentioning
confidence: 95%
“…AVP neurons display in vitro an electrical activity almost comparable with that observed in vivo, characterized by a succession of shorter periods of activity and silence than in vivo (23). Electrical stimulations of isolated neurohypophysial terminals led to the demonstration that the silent and active periods in the firing activity of AVP neurons are equally necessary for optimal release (24,25). SDF-1, as shown here, has various effects on the electrical activity of SON neurons, resulting probably from the heterogeneity of the population recorded or from a variety of actions on the AVP neuronal population (26).…”
Section: Discussionmentioning
confidence: 95%
“…During dehydration, while the increased somatodendritic release of AVP (33) will optimize phasic activity, facilitating systemic AVP release (ref. 32 and see references therein), apelin accumulates in SON and PVN neurons, instead of being systemically and probably intranuclearly released. Thus, decreased local supply of apelin to SON and PVN AVP cell bodies may facilitate the expression by AVP neurons of an optimized phasic activity, by lowering the inhibitory action of apelin on these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In response to osmotic stimulation, an increased somatodendritic release of AVP from SON and PVN cell bodies occurs (32,33), enhancing by means of V1 autoreceptors the phasic activity pattern of AVP neurons (32) and thereby facilitating systemic AVP release. In a similar way, apelin may be involved in autocrine somatodendritic feedback regulation of neurohypophyseal AVP neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have shown that during exposure of rats to air-jet stress, selective blockade of central VP receptors do not affect the response of the hypothalamo-pituitary axis as judged by the concentration of blood corticosterone (Stojičić et al, 2008), suggesting that VP released into the portal circulation during air-jet stress does not modulate ACTH release into the blood stream. Nonetheless, physiological stimuli know to increase VP release into the blood stream, such as hyperosmotic challenge, have been reported to increase intranuclear release of VP (Son et al, 2013) and that its role is to coordinate the optimal firing rate of the whole population of magnocellular neurons (Gouzènes et al, 1998), and also to activate pre-sympathetic neurons in the parvocellular division of PVN. This inter-neural cross-talk has been shown to involve V1aRs in PVN (Son et al, 2013), supporting the present findings.…”
Section: Discussionmentioning
confidence: 99%